Peran Literasi Keuangan Digital, Pendidikan, Sikap Keuangan, dan Pendapatan Terhadap Pengelolaan Keuangan Generasi Sandwich di Kabupaten Indramayu - Rosita Rosita; Pradana Jati Kusuma; Rudi Kurniawan; Amalia Nur Chasanah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The phenomenon of the sandwich generation is increasingly prominent in Indramayu Regency with the increasing burden on the family economy and the development of digital financial services. This generation is at a productive age but has to bear the needs of two generations at once, so financial management skills are very crucial. This study aims to examine the influence of the role of digital financial literacy, education, financial attitudes, and income on the management of the sandwich generation in Indramayu Regency . This study applied a quantitative approach with purposive sampling technique on 115 respondents after screening. Data was collected through a Likert scale questionnaire and analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4. The results of the study explained that financial attitudes and income have a positive and significant effect on financial management. In contrast, digital financial literacy and education did not show a significant influence. The R-Square value of 0.592 explains that the model has moderate explanatory ability. These findings indicate that behavioral factors and actual economic conditions determine the quality of financial management of the sandwich generation more than formal knowledge and digital literacy.